From Snapshots to Movies: The Association Between Retirement Sequences and Aging Trajectories in Limitations to Perform Activities of Daily Living. (February 2019) - Azar, Ariel; Staudinger, Ursula M.; Slachevsky, Andrea; Madero-Cabib, Ignacio; Calvo, Esteban
Objective: This study analyzes the dynamic association between retirement sequences and activities of daily living (ADLs) trajectories between ages 60 and 70.Method: Retirement sequences previously established for 7, 880 older Americans from the Health and Retirement Study were used in hierarchical linear and propensity score full matching models, analyzing their association with ADL trajectories.Results: Sequences of partial retirement from full- or part-time jobs showed higher baseline and slower decline in ADL than sequences characterized by early labor force disengagement.Discussion: The conventional model in which people completely retire from a full-time job at normative ages and the widely promoted new conventional model of late retirement are both associated with better functioning than early labor force disengagement. But unconventional models, where older adults keep partially engaged with the labor force are also significantly associated with better functioning. These findings call attention to more research on potential avenues to simultaneously promote productive engagement and health later in life.